“Égua”, é a hora do intervalo na tv: marcadores sociais da diferença, consumidores/as e publicidade produzida em Belém do Pará - OLIVEIRA, Robson Cardoso de (Universidade Federal do Pará, 2017)
This dissertation is "born" with a mission: to investigate on the receipt of social markers of the difference between the advertising consumers produced in the city of Belém, Pará, in order to observe how the categories of Gender and Sexuality are received and (re) signified at the moment we watch the interval time in TV. However, other social markers of difference as Class, Color/Race and Generation were added by consumers in conversations, and consequently were problematized in this study. In addition, discussions about advertising and consumption also gained prominence as a consequence of the very strength of the consumers’ speeches. As a result, I realized that social markers of difference were being operated in the narratives in an intersected (or articulated) mode, among these, the most active in this tangency were the Gender, Color/Race and Class categories, comprised by speeches as: black and poor male; and white and rich woman. The "game" between the real and the "magical" world of ads (Rocha 1990), also commented out by consumers, viewing the advertising much closer to real idealizations, instead of showing the realities at the interval time in TV.